Subxiphoid-subcostal thoracoscopic thymectomy for seropositive myasthenia offers equivalent remission rates and potentially faster recovery. (18th November 2021) - Cao, Peng; Hu, Shan; Qu, Wensheng; Kong, Kangle; Han, Peng; Yue, Jiaqi; Deng, Yu; Fu, Xiangning; Li, Fan; Zhao, Bo
Abstract: OBJECTIVES: To compare the perioperative and follow-up outcomes of patients with myasthenia gravis (MG) receiving subxiphoid-subcostal or unilateral thoracoscopic thymectomy and to identify the factors affecting MG prognosis. METHODS: From January 2013 to December 2019, a total of 137 consecutive MG patients received subxiphoid-subcostal thoracoscopic thymectomy (STT, n = 65) or conventional unilateral thoracoscopic thymectomy (UTT, n = 72). The primary outcomes of this study were perioperative complications, duration and expenses of hospitalization, VAS score and complete stable remission (CSR). RESULTS: The patients receiving STT had significantly shorter drainage duration and postoperative hospital stay and lower hospitalization expenses ( P < 0.01). Pain scores on postoperative Days 1, 3, 7 and 14 were significantly lower in patients undergoing STT ( P < 0.01). The average follow-up was 54.3 ± 24.18 months, with a CSR rate of 30.6% and an overall effective rate of 87.3%. Through uni- and multivariable analyses, shorter symptom duration and Myasthenia Gravis Foundation of America (MGFA) class I were independent predictors for CSR in MG patients receiving thymectomy. CONCLUSIONS: The present study not only showed that STT was a safe and feasible technique for MG, with a potentially faster postoperative recovery, lower hospitalization expenses, less postoperative pain and equivalent remission rate, but also revealed that shorter symptom duration and MGFA class I were favourable prognostic factors for CSR. Abstract : Myasthenia gravis (MG) is a long-lasting and rare autoimmune disease caused by neuromuscular junction dysfunction and characterized by weakness and abnormal muscle fatigue [1, 2].